Impact of Elements of Quality of Work Life: Applied Study on Civil Service Employees in Saudi Arabia - AlAmri, Mohammad; Alyafi, Randa (Jordan Journal of Business Administration, 2017)
The aim of this research study is to identify the impact of the elements of quality of work life affecting the performance of civil service employees and measure the differences between some demographical factors and: overall performance, performance appraisal, job satisfaction, relationship between the employee and his/ her superiors and colleagues, financial and non-financial incentives and the work environment. The study adopted the descriptive analytical method and used a questionnaire distributed to (2,500) employees in Civil Service, Kingdom of Saudi Arabia. Data showed that the most influential factors of quality of work life affecting performance are: the relationship between the employee and his/ her superiors and colleagues, job satisfaction, financial incentives and performance evaluation. Furthermore, the data found statistically significant differences in job performance, job satisfaction, the relationship between the employee and his/ her superiors and colleagues, financial and non-financial incentives and work environment and some demographical factors: ranking position, age, education, years of experience and marital status.